Syphilis and HIV prevalence and associated factors to their co-infection, hepatitis B and hepatitis C viruses prevalence among female sex workers in Rwanda - Mwumvaneza Mutagoma (BMC Infectious Diseases, 2017)
Abstract Background Human Immunodeficiency Virus (HIV), syphilis, Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) are sexually transmitted infections (STIs) and share modes of transmission. These infections are generally more prevalent among female sex workers (FSWs). Methods This is a cross-sectional study conducted among female sex workers (FSWs) in Rwanda in 2015. Venue-Day-Time (VDT) sampling method was used in recruiting participants. HIV, syphilis, HBV, and HCV testing were performed. Descriptive analyses and logistic regression models were computed. Results In total, 1978 FSWs were recruited. The majority (58.5%) was aged between 20 and 29 years old. Up to 63.9% of FSWs were single, 62.3% attained primary school, and 68.0% had no additional occupation beside sex work. Almost all FSWs (81.2%) had children. The majority of FSWs (68.4%) were venue-based, and most (53.5%) had spent less than five years in sex work. The overall prevalence of syphilis was 51.1%; it was 2.5% for HBV, 1.4% for HCV, 42.9% for HIV and 27.4% for syphilis/HIV co-infection. The prevalence of syphilis, HIV, and syphilis + HIV co-infection was increasing with age and decreasing with the level of education. A positive association with syphilis/HIV co-infection was found in: 25 years and older (aOR = 1.82 [95% CI:1.33–2.50]), having had a genital sore in the last 12 months (aOR = 1.34 [95% CI:1.05–1.71]), and having HBsAg-positive test (aOR = 2.09 [1.08–4.08]). Conclusion The prevalence of HIV and syphilis infections and HIV/syphilis co-infection are very high among FSWs in Rwanda. A strong, specific prevention program for FSWs and to avert HIV infection and other STIs transmission to their clients is needed.